Relationships between irregular pulsation and variations in morphological characteristics during the cardiac cycle in unruptured intracranial aneurysms by 4D-CTA - Shiyao Chen; Nan Lv; Yu Qian; Mingwei Zhang; Tianyi Zhang; Yunzhang Cheng (Frontiers in Neurology, 2024)
Background and purposeIrregular pulsation of the aneurysmal wall has been suggested as a novel predictor for aneurysm rupture. Aneurysm volume variations during the cardiac cycle and the association between irregular pulsation and morphological features have been discussed, but the clinical significance remains unclear. The purpose of this study was to quantify changes in morphological characteristics over the cardiac cycle and examine their correlation with irregular pulsation to facilitate comprehension of aneurysm dynamics.Materials and methodsFourteen unruptured intracranial aneurysms (UIAs) from 11 patients were included in this study, and each of them underwent 4D-CTA after diagnosis by DSA. The R-R intervals were divided into 20-time phases at 5% intervals to determine whether an aneurysm had irregular pulsation throughout the cardiac cycle. CT images from the 20-time phases were used to reconstruct 3D aneurysm models, measure 14 morphological parameters, and quantify each parameter’s absolute change and relative rates of change during the cardiac cycle.ResultsSeven of 14 UIAs exhibited irregular pulsation over the cardiac cycle by 4D-CTA, 5 of which were small aneurysms (< 7 mm). The UIAs with irregular pulsation exhibited greater changes in morphological characteristics. As aneurysm size increased, the absolute change in aneurysm volume increased (p = 0.035), but the relative rates of change in aneurysm size (p = 0.013), height (p = 0.014), width (p = 0.008), height-to-width ratio (p = 0.009), dome-to-neck ratio (p = 0.019) and bottleneck factor (p = 0.012) decreased.ConclusionAlthough the larger the aneurysm, the greater the amplitude of its volumetric variation, small aneurysms are prone to irregular pulsation during the cardiac cycle and have more pronounced and dramatic morphological changes during the cardiac cycle that may increase the risk of rupture. This proof-of-concept study could help to explain the importance of dynamic changes using 4D-CTA in assessing the rupture risk of UIAs.